2011
DOI: 10.4061/2011/238549
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Bacillus licheniformis Alkaline Protease from Supernatant of Fermented Wastewater Sludge Using Ultrafiltration and Its Characterization

Abstract: Investigation on recovery of alkaline protease from B. licheniformis ATCC 21424 fermented wastewater sludge was carried out by centrifugation and ultrafiltration. Optimization of ultrafiltration parameters (transmembrane pressure (TMP) and feed flux) was carried out with 10 kDa membrane. TMP of 90 kPa and feed flux of 714 L/h/m2 gave highest recovery (83%) of the enzyme from the centrifuged supernatant. The recovered enzyme had given maximum activity at temperature of 60°C and at pH 10. It was stable between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 44 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…These results suggest that this enzyme is a thermophilic protease. Some proteases, the optimum temperature of which was 60 °C, have also been reported, which are B. licheniformis ATCC 21424 47 , B. mojavensis A21 8 , Bacillus sp. SM2014 46 , and A.veronii PG01 48 .…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that this enzyme is a thermophilic protease. Some proteases, the optimum temperature of which was 60 °C, have also been reported, which are B. licheniformis ATCC 21424 47 , B. mojavensis A21 8 , Bacillus sp. SM2014 46 , and A.veronii PG01 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, protease activity was not detected in permeate as the size of alkaline proteases produced were in range between 26-100 kDa. Some studies reported that there was no protease activity detectable in all permeates due to the lost as a deposit in the membrane of the tube (Bezawada et al, 2011). However, during lyophilisation the loss of activity resulted in 21%, being this step the most critical for the recovery of protease.…”
Section: Enzymatic Activity Profile and Extractionmentioning
confidence: 99%
“…It well established that pH is a key factor influencing the ionization state of the amino acid or ionization of the substrate and thereby the expression of the enzyme activity (Bezawada et al, 2011). In the present study, the relative protease activity measured at different pH ranging from 6 to 10 (Figure 3) showed maximum activities at pH 9 (88.69 ± 1.71).…”
Section: Effect Of Ph On the Stability And The Optimum Activity Of Thmentioning
confidence: 54%
“…The result presented in Table 1 protease activity; this may be due to the activation by the metal ions (Bezawada et al, 2011;Kumar et Takagi, 1999 showed maximum inhibition on enzyme activity up to 60%, while Hg + inhibited the enzyme activity up to 35%. Analogous results were found for the A. pullulan, A. terreus and B. subtilis , Niyonzima and More, 2015, and Alam et al, 2017.The inhibitory effect of mercury was due to the fact that it reacts with protein thiol groups and with histidine and tryptophan residues (Bezawada et al, 2011, Barth andGaillardin, 1997).…”
Section: Effect Of Metal Ion On the Enzyme Activitymentioning
confidence: 99%